Association of Race With Risk of Incident Cardiovascular Disease, Coronary Heart Disease, Heart Failure, and Stroke - Michael J. Domanski, MD; Colin O. Wu, PhD; Xin Tian, PhD; Haiou Li, PhD; Ruba Shalhoub, MS; Rui Miao, PhD; Ahmed A. Hasan, MD, PhD; Yi Huang, PhD; Jared P. Reis, PhD; Jerome L. Fleg, MD; Jamal S. Rana, MD; Kai Zhang, PhD; et al. (JACC: Advances)
Background: In prior studies of cumulative risk factor exposure, self-identified race was independently associated with incident cardiovascular disease (CVD). A recent study suggests clinical, demographic, and socioeconomic factors explain racial differences. We used propensity score matching to study race as an independent incident CVD risk factor. Objectives: The purpose of this study was to assess race as an independent risk factor for incident CVD. Methods: We analyzed CARDIA (Coronary Artery Risk Development in Young Adults) study data using propensity score matching of White and Black women, and, separately, White and Black men, with respect to known CVD risk factors. Results: Black men (n = 487), compared to White men (n = 487), had higher risk of CVD (HR: 2.30; 95% CI: 1.36-3.89; P = 0.0014), stroke (HR: 5.00; 95% CI: 1.45-17.3; P = 0.0047), and congestive heart failure (CHF) (HR: 3.60; 95% CI: 1.34-9.70; P = 0.0067). Black women (n = 640), compared to White women (n = 640), had higher CVD risk (HR: 2.36; 95% CI: 1.17-4.78; P = 0.014) and stroke risk (HR: 2.80; 95% CI: 1.01-7.77; P = 0.039) and borderline significantly higher CHF risk (HR: 3.50; 95% CI: 0.73-16.9; P = 0.096). Risk of coronary heart disease did not differ significantly by race in either sex. Multivariable analyses showed racial differences in the associations of multiple risk factors with incident CVD events independent of other known CVD risk factors. Conclusions: Propensity score matching analyses demonstrate that race is an independent risk factor for incident CVD and its components, CHF, and stroke. Multivariable analyses suggest racial differences in Black vs White risk factor impact as the possible cause. Reasons for these differences remain to be explored.